A Model for the Sustainable Development of the Traditional Food Industry as a Support for Food Security Using the Dematel and ISM Approaches - Lukman Achmad; Muhaimin (Institut Manajemen Wiyata Indonesia, 2026)
Traditional food SMEs play a very important role in national economic growth and development. Therefore, it is essential to develop traditional food SMEs in a sustainable manner. This study focuses on the driving factors for the successful and sustainable development of traditional food SMEs. It seeks to explore the hierarchy, interrelationships, and strength of factors that play important roles in the development of these SMEs. To address the research questions, a survey was conducted. The respondents comprised 12 SME actors engaged in producing and selling wajit and gurilem in West Bandung Regency, West Java Province. The respondents also included four community leaders, two sub-district officials, four academics, and 25 consumers. This study employed a mixed-methods design. Data were collected through interviews, surveys, and secondary sources from August to October 2024. The Interpretive Structural Modeling (ISM) method was used to construct the hierarchical structure of factors, while the Decision-Making Trial and Evaluation Laboratory (DEMATEL) approach was applied to analyze cause-and-effect relationships. MICMAC analysis was also conducted to classify factors based on driving power and dependence. The results indicate that, of the 15 factors examined, three factors act as linkage factors (i.e., marketing, product development, and business networks); six factors are categorized as dependent (i.e., technology and digitalization, internationalization, and socio-cultural factors); and six factors are categorized as independent (i.e., managerial skills, business models, entrepreneurial skills, financial resources, innovation, and human resource capacity). The findings reveal that managerial skills, business models, entrepreneurial skills, financial resources, innovation, and human resource capacity are critical factors that should receive primary attention in the sustainable development of traditional food SMEs.